Bioactive compounds with DNA-binding and antibiotic properties from marine sediment microorganisms - Aloot, Haide May (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2007)
The marine environment has recently become the focus of intensive investigation in the global search for new drugs. Aside from marine invertebrates and algae, a number of microorganisms have been shown to synthesize compounds with a variety of specific bioactivities. As a continuing research program in our laboratory, we targeted on screening of sediment microorganisms obtained from an estuarine environment near the Layawan River in Oroquita City Misamis Occidental. Using our own modification of a novel screening protocol employing a combination of biomolecular (DNA-binding)-chemical (one and two-dimensional thin layer chromatography) techniques, we were able to identify several actinomycetes (Nocardia sp., Actinomyces sp., and Streptomyces sp.), non-filamentous bacteria (Listeria sp., Corynebacterium sp., and Bacillus sp.), and fungi (Aspergillus sp., Rhizopus sp. and Penicillin sp.) that produce putative DNA-binding antibiotics. The assay was analogous to gel retardation assays but done on preparative TLC plates rather than on agarose gel in electrophoretic systems. Further, we also introduced a two-level antibiotic production screening to target only putative antibiotics with DNA-binding properties. Our modification has the potential for shortening the screening process for new potent drugs based on DNA-binding properties of microbial metabolites. DNA-binding is a definite indicators of gene regulatory function exemplified by peptides which are anti-tumor antibiotics. Therefore, the most significant result of our study is the demonstration of production of similar bioactive metabolites by our microbial isolates using a modified biomolecular-chemical screening procedure. This will certainly have a profound impact on the local pharmaceutical industry in the near future.